PENGUATAN PERAN PEMUDA KARANG TARUNA SEBAGAI UPAYA MENCIPTAKAN AGEN PERUBAHAN SOSIAL DI DESA CIBIRU HILIR, KABUPATEN BANDUNG - Lesmana, Aditya Candra; Yunita, Desi (Universitas Padjadjaran, 2025)
In Hamlet 4 of Cibiru Hilir Village, it is known that there is an active youth organisation in all neighbourhoods. However, it is also known that the existing youth organisation experiences a decline in youth interest in joining social organisations such as youth groups. This problem arises partly because the youth do not understand their role as agents of social change through participation in youth organisations. In addition, youth who are members of the youth group also lack an understanding of how to manage a good organisation, including creating programmes through problem and potential mapping to align with village development goals. The purpose of this community service is to increase understanding of the role of youth in the youth organisation as agents of social change in Hamlet 4, Cibiru Hilir. The method used is training and education, with the stages of activities starting from mapping the potentials and problems in Cibiru Hilir Village, analysing and determining programmes, preparing training materials, and implementing and evaluating the training activities. The results of the training showed a better understanding of the role of youth in Karang Taruna as agents of social change in their neighbourhood. Participants also understood how to map potentials and problems using SWOT analysis as a tool to create programmes that suit their needs. In addition, the results of this training also increased the motivation of the youth who participated in the training to join Karang Taruna and to create creative and innovative programmes in an effort to support village development goals. Pada Dusun 4 Desa Cibiru Hilir diketahui memiliki karang taruna yang aktif di seluruh RW yang ada. Meskipun aktif, diketahui terjadi penurunan minat pemuda untuk bergabung dalam karang taruna. Permasalahan ini muncul salah satunya karena para pemuda kurang memahami peran sebagai agen perubahan sosial melalui keikutsertaan dalam karang taruna. Selain itu, pemuda yang tergabung dalam karang taruna juga kurang memahami bagaimana manajemen organisasi yang baik, pembuatan program melalui pemetaan permasalahan dan potensi untuk menyelaraskan program dengan tujuan pembangunan desa. Tujuan pengabdian pada masyarakat ini adalah untuk meningkatkan pemahaman peran pemuda dalam karang taruna sebagai agen perubahan sosial di Dusun 4 Cibiru Hilir. Metode yang digunakan adalah pelatihan dan edukasi dengan tahapan kegiatan dimulai dari pemetaan potensi dan permasalahan di Desa Cibiru Hilir, analisis dan penentuan program, persiapan program pelatihan, dan tahap pelaksanaan serta evaluasi kegiatan pelatihan. Hasil dari pelatihan yang dilakukan menunjukkan adanya pemahaman yang lebih baik terkait peran pemuda dalam karang taruna sebagai agen perubahan sosial di lingkungan tempat tinggalnya. Peserta pelatihan juga menjadi memahami bagaimana melakukan pemetaan potensi dan permasalahan dengan menggunakan analisis SWOT sebagai media untuk menciptakan program yang sesuai dengan kebutuhan. Selain itu hasil dari pelatihan ini juga meningkatkan motivasi pemuda yang mengikuti pelatihan untuk bergabung dalam karang taruna dan menciptakan program yang kreatif dan inovatif dalam upaya mendukung tujuan pembangunan desa.